Acid-pepsin soluble collagen from saltwater and freshwater fish scales - Upasen, Settakorn (Animo Repository, 2019)
Extraction and characterization of acid soluble collagen (ASC) and pepsin soluble collagen (PSC) from scales of Giant groupers (saltwater fish) and Nile tilapia (freshwater fish) were carried out in this research. Due to a higher protein content in scales, collagen yield extracted from the Giant groupers scales was higher than that of the Nile tilapia scales. The yield increased as extraction time increased for both ASC and PSC and pepsin extraction resulted in higher yields than acid extraction. Even though there were differences in collagen yields, collagen characteristics were independent of the scale sources but some differences were observed for the ASC and PSC. The peptide hydrolysis patterns of the ASC showed a wide range of molecular weights whereas all of the PSC had similar molecular weight of around 42 kDa. FTIR spectra showed that all the collagens remained the triple helical structure though ASC might be self-aggregated. From zeta potential analysis, net charge of zero was found at pH 3.2-4.0 and the dynamic light scattering suggested that the average particle sizes at pH 11-12 were around 100-200 nm. The denaturation temperatures (Tds) in a range of 35-42oC indicated that the collagens were considerably thermally stable. © 2019, Chulalongkorn University, Faculty of Fine and Applied Arts. All rights reserved.